Organizational Structure, Subsystem Interaction Pattern, and Misalignments in Complex NPD Projects - Jafari Songhori, Mohsen; Nasiry, Javad (Production and Operations Management, 2020)
Developing a complex new product requires the firm both to deconstruct that product into subsystems and to create an organizational structure aligned with the product architecture. However, empirical evidence indicates that misalignments do occur and are usually one of two general forms: a “hidden dependency,” which is a missing link between teams responsible for two interacting subsystems; or “spurious communications” between two teams that interact even though their respective subsystems are not linked. We model the product development process as a search on a rugged landscape and study how misalignments affect the performance of the process in both design quality and convergence time. We find that the effects are mediated by the organizational decision‐making structure, and also by the interaction pattern among product subsystems. For instance, with a modular design, a project with a hidden dependency yields higher quality design solutions than a project with spurious communications or an aligned project. However, hidden dependencies cause a longer convergence time. Further, in modular designs spurious communications do not impact quality or convergence time when compared with aligned projects. The effect in non‐modular product designs depends on the organizational decision‐making structure and managerial capability. When decisions are made in a centralized organization that employs a capable manager, spurious communications improve the design quality but could delay the convergence time. We trace the cause of these effects to errors committed by teams in rejecting superior designs, which make the search process more exploratory and covering a wider area of the search landscape.